Learning Perl Objects, References & Modules - Schwartz, Randal L. (O'Reilly, 2011)
Learning Perl Objects, References & Modules picks up where Learning Perl leaves off. This new book offers a gentle introduction to the world of references, object-oriented programming, and the use of Perl modules that form the backbone of any effective Perl program. Following the successful format of Learning Perl, each chapter in the book is designed to be small enough to be read in just an hour or two. Each chapter ends with a series of exercises to help you practice what you've learned with answers in an appendix for your reference. In short, this book covers everything that separates the Perl dabbler from the Perl programmer.